2019
DOI: 10.48550/arxiv.1910.10812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Avalanche induced co-existing localised and thermal regions in disordered chains

Philip J. D. Crowley,
Anushya Chandran

Abstract: We investigate the stability of an Anderson localised chain to the inclusion of a single finite interacting thermal seed. This system models the effects of rare low-disorder regions on many-body localised chains. Above a threshold value of the mean localisation length, the seed causes runaway thermalisation in which a finite fraction of the orbitals are absorbed into a thermal bubble. This 'partially avalanched' regime provides a simple example of a delocalised, non-ergodic dynamical phase. We derive the hiera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…Moreover, we demonstrate that this emergent ergodicity is intimately tied to the presence of a phase transition; a disorder-less, symmetry-breaking field suppresses the intervening ergodic phase. In addition to numerics, we analyze two instabilities which could induce thermalization near the putative transition: (i) the proliferation of two-body resonances [2,31,32] and (ii) the run-away of avalanches [33,34]. We find that the latter is marginal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we demonstrate that this emergent ergodicity is intimately tied to the presence of a phase transition; a disorder-less, symmetry-breaking field suppresses the intervening ergodic phase. In addition to numerics, we analyze two instabilities which could induce thermalization near the putative transition: (i) the proliferation of two-body resonances [2,31,32] and (ii) the run-away of avalanches [33,34]. We find that the latter is marginal.…”
mentioning
confidence: 99%
“…Alternatively, one might consider the susceptibility to 'avalanches' due to rare thermal bubbles induced by the interactions [33,67,68]. For a system with a distribution of localization lengths, it has recently been shown that the average localization length controls this instability [34]: for ξ > 2/ log 2, thermal bubbles avalanche. However, this is within a model where the orbitals have a single localization center.…”
mentioning
confidence: 99%
“…Refs. [68,69]. Chaos manifests in the exponential scaling of the Frobenius norm of the AGP with system size, which can be interpreted as an exponential sensitivity of the eigenstates to perturbations of the Hamiltonian.…”
Section: Chaotic But Non-ergodic Regimementioning
confidence: 99%